Заліщицька локальна група трипільської культури: питання історіографії - Яковишина, Я. (Інститут українознавства ім. І. Крип'якевича НАН України, 2009)
Trypil’s’ka culture in scientific literature is divided into several local variants which have chronological, territorial and cultural peculiarities. Zalischytskyi variant has the longest history of exploration. It was distinguished in the beginning of XX century by O. Kandyba. Despite of long history of researches, it is still many important issues, which are not solved.